Is Ignatian Spirituality an Environmental Friendly Spirituality? (Hekima Review, 2010)
This article seeks to explore the Ignatian Spirituality in the light of the current environmental crisis. It seeks to find out if this spirituality can be proposed as a paradigm through which the Christian community can effectively relate with their environment. It poses this question because spirituality is an integrated way of life through which a person comes in touch with an ultimate reality or transcendent dimension of the world, and through it discover the essence of his or her being. In other words, spiritualities help one to come to a grip of the “deepest values and meanings by which people live”. In the Christian/Catholic parlance, where Ignatian Spirituality belongs, spirituality brings a believing faithful into the practice of living out a personal act of faith.